2012
DOI: 10.1590/s1679-62252012005000021
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal steroids levels and vitellogenesis in the formation of oocytes in Prochilodus lineatus (Valenciennes) (Teleostei: Characiformes)

Abstract: The objective of this study was to obtain information about the possible mechanisms related to poor reproductive performance in tropical rheophilic fish. To that effect, cages (Cs) and earthen ponds (EPs) were used as experimental systems to provide unsuitable and suitable conditions, respectively, for curimbatá (Prochilodus lineatus) breeders. Fish were maintained under experimental conditions for 18 months, and during this period females were randomly sampled every two months for biometric analysis (n=30), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…In other studies, however, has been no such correlation (Linhares et al, 2014). In this population the size of the oocytes can also be affected adverse habitat (Hainfellner et al, 2012) and how many times they consisted of female eggs (in the first spawning are larger oocytes) (Kjesbu, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, however, has been no such correlation (Linhares et al, 2014). In this population the size of the oocytes can also be affected adverse habitat (Hainfellner et al, 2012) and how many times they consisted of female eggs (in the first spawning are larger oocytes) (Kjesbu, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The vitellogenic process of H. marginatus was like that of other tropical Characiformes rheophilic species (Hainfellner, Souza, et al, ; Schorer et al, ), occurring in October or November, approximately 2 months before the spawning season (spring/summer). In the first reproductive cycle, an abrupt increase in E 2 levels between November and December was concomitant with a GSI elevation and with the occurrence of maturing and mature females.…”
Section: Discussionmentioning
confidence: 72%
“…Similar to that of its congener, Hypophthalmus edentatus (Carvalho, ), H. marginatus exhibited a very well‐defined spawning season from November to February that was more intense from November to December. We described a long resting period (approximately six months during the autumn and winter months) typical of migratory total spawners in natural (Alvarenga, Bazzoli, Santos, & Rizzo, ; Lima‐Junior & Goitein, ; Narahara, Basile‐Martins, Godinho, & Cipolli, ) or captive conditions (Ganeco, Nakaghi, Urbinati, Dumont‐Neto, & Vasques, ; Hainfellner, Souza, Moreira, Nakaghi, & Batlouni, ; Schorer, Moreira, & Batlouni, ). All these characteristics indicate that the species presents a reproductive cycle typical of tropical migratory total spawners (Borella et al, ; Rizzo & Bazolli, ; Vazzoler, ; Zaniboni‐Filho & Nuñer, ); however, the presence of three batches of oocytes in mature females indicated that the species may spawn more than once within the same breeding season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mance in culture, highlighting the fast growth and good use of low quality foods (Croux, 1992). Several studies were performed on the histology of the digestive tract (Domitrovic, 1983), reproduction (Croux;Hainfellner et al, 2012), embryonic development (Botta et al, 2010) and growth (Furuya et al, 1999). On the other hand, studies on abundance as part of ichthyoplankton were also carried out in relation to the growth chronology from yolk larvae stage to juvenile (Sverlij et al, 1993;Fuentes, 1998).…”
Section: Introductionmentioning
confidence: 99%